Efficacy of a 6-Week Home-Based Online Supervised Exercise Program Conducted During COVID-19 in Patients With Post Percutaneous Coronary Intervention: A Single-Blind Randomized Controlled Trial - Li, Jiajia; Liu, Bo; Wang, Zheng; El-Ansary, Doa; Adams, Roger; Han, Jia; Meng, Shu (Frontiers in Cardiovascular Medicine, 2022)
Objective The aim of this study was to assess the efficacy of a 6-week cardiac rehabilitation (CR) program designed for patients with coronary artery disease (CAD) after percutaneous coronary intervention (PCI) that involved an online supervised exercise program that they could access during COVID-19. Methods One hundred patients were randomly allocated into control group (CG) and supervision group (SG). CG accepted conventional health education with a home exercise program booklet delivered before discharge, SG had an additional home-based online supervised exercise program (HOSEP). Questionnaires, motor function and lipid profile were administered at baseline. Questionnaires included the Godin-Shephard Leisure-Time Physical Activity questionnaire (GSLTPAQ) and Bandura's Exercise Self-efficacy (ESE). Motor function included: 6-min walk test (6 MWT), timed up and go test (TUG), 30-s sit to stand (30-s STS), and Hand Grip Strength (HG). Lipid profile included: low-density lipoprotein (LDL), high-density lipoprotein (HDL), total cholesterol (TC) and triglycerides (TG). The questionnaires were re-administered after 2-weeks, all tests were re-evaluated after 6-weeks. Results the questionnaire results showed that scores on GSLTPAQ and ESE were significantly improved in the SG. The changes in GSLTPAQ scores from baseline to 2- and 6-weeks in the SG were significantly higher than in the CG (2-week: 6.9 ± 13.0 for SG and 0.2 ± 10.2 for CG, p = 0.005; 6-week: 9.4 ± 18.1 for SG and 0.2 ± 11.8 for CG, p = 0.003). in terms of motor function, both the CG and SG improved TUG and 6 MWT performance, with the 6 MWT improvement being significantly greater in the SG than CG (43.7 ± 39.2 m for SG and 16.6 ± 39.1 m for CG, p = 0.001). Improvement in the 30-s STS was significantly greater in the SG than CG (2.4 ± 3.6 repetitions for SG and 0.4 ± 3.5 repetitions for CG, p = 0.007). the lipid profile level significantly improved over baseline in both SG and CG after 6-week intervention, and these changes were not statistically different between groups. Conclusion This pilot randomized control study demonstrated that a 6-week HOSEP, when added to education delivered pre-hospital discharge for CAD patients following PCI, was beneficial with respect to exercise self-efficacy, exercise behavior, motor function and lipid profile. Supervised exercise programs delivered online in addition to education providing effective and accessible CR during COVID-19.